The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/09610006211053043
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of emerging COVID-19 research trends and future implications for LIS field: A bibliometric mapping and visualization

Abstract: The COVID-19 epidemic has proved a nightmare for human beings living all across the globe. It has severely affected all segments of human life. Consequently, enormous research has been conducted to assess and counter this global pandemic. This study reports finding of a bibliometric analysis on COVID-19 related literature published in the Library and Information Science journals, to identify current research trends and to suggest future directions for further research. It reveals a substantial increase in LIS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…In 2020, the average number of papers per month was about 20, but in 2021, the number doubled (Table 2). Previous studies have also identified already that COVID-19 publications are on the rise over time (Kambhampati et al, 2020;Sheikh et al, 2021;Torres-Salinas et al, 2020). In addition to exploring quantitative growth, this study obtained bibliometric analysis results of various aspects on the publication of COVID-19 in the LIS journals: top country-USA, the most prolific institution-Harvard University, and the most productive outlet-Journal of the American Medical Informatics Association.…”
Section: Summary and Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In 2020, the average number of papers per month was about 20, but in 2021, the number doubled (Table 2). Previous studies have also identified already that COVID-19 publications are on the rise over time (Kambhampati et al, 2020;Sheikh et al, 2021;Torres-Salinas et al, 2020). In addition to exploring quantitative growth, this study obtained bibliometric analysis results of various aspects on the publication of COVID-19 in the LIS journals: top country-USA, the most prolific institution-Harvard University, and the most productive outlet-Journal of the American Medical Informatics Association.…”
Section: Summary and Discussionmentioning
confidence: 95%
“…Nevertheless, the bibliometric study on COVID-19-related publications in LIS field deserves more interest. Sheikh et al (2021) reviewed 501 LIS publications on the topic of COVID-19 by searching in the Scopus . They found that a good range of bibliometric study on COVID-19 has been published on LIS journals.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Keywords "Covid-19", "Library Services", "Public Libraries", "Social Media", "Closed", "Library Users", "Social Networks", "Technologies" and "Information and communication" are among the most frequent keywords in this cluster. Sheikh et al, (2021) in the cluster of "Libraries and information society" investigated the role of libraries in the information society. Social networks such as Twitter, Facebook, YouTube, Instagram and WhatsApp, are the most important keywords in this cluster.…”
Section: Discussionmentioning
confidence: 99%
“…The basic result concluded in this research that Information Management Department at the University of the Punjab is the significant contribution in LIS literature. Further bibliometric studies have been conducted by various authors for statistical information such as (N. Farooq, Rehman, Ashiq, Siddique, & Ahmad, 2021;Sheikh, Siddique, Qutab, Khan, & Mahmood, 2021;Shoaib, Ahmad, Ali, & Abdullah, 2021;Siddique, Rehman, Ahmad, Abbas, & Khan, 2021;Singh, Mittal, & Ahmad, 2007;Tijjani, Ashiq, Siddique, Khan, & Rasul, 2020) It is needed to additionally comprehend to recount the narrative of a major dataset indeed, what the library terms which have been analyzed. Consequently, an understanding regarding the bibliometric research could be valuable.…”
Section: Literature Reviewmentioning
confidence: 99%